A Call to Action on Point-of-Care Violence in Hospitals and Health Systems. (March 2019) - Boston-Fleischhauer, Carol; Herleth, Anne; Langr, Madeleine
Abstract : Despite deeper investment in security measures, the rate of violence and point-of-care safety threats in healthcare settings is rising. As a result, nurses do not always feel safe while delivering care. In this article, the authors describe strategies for addressing point-of-care violence. This is the 2nd article of a series. The 1st article of this series, Cracks in the Foundation of the Care Environment Undermine Nurse Resilience, in the December 2018 issue (volume 48, issue 12) of The Journal of Nursing Administration, the authors explained how nursing leaders can reduce frontline nurse stress and burnout by addressing 4 "cracks in the foundation" of the care environment that can undermine nurse resilience. This article aims to help leaders address 1 of the foundational cracks: that violence and point-of-care safety threats are now commonplace in healthcare settings.